Biocuration and biodiversity: process, successes, failures, solutions and perspectives - Castillo, Maribel; Michán, Layla; Martínez, Armando Luis (Instituto de Ecología, A.C., 2014)
The curation of biological digital data or biocuration is the activity of organizing, representing and making biological information accessible to human beings through computers. Among its tasks are the organization, standardization, normalization, classification, annotation and analysis of information. The National System of Information on Biodiversity (SNIB) from the National Commission for Knowledge and Use of Biodiversity (CONABIO) integrates information of about six million records of biological organisms and observations mainly from zoological collections and herbaria in Mexico. To manage this information CONABIO has established quality control mechanisms of the data that are included in the SNIB, that allows to integrate the information of different sources and make it consistent and interoperable with other information systems. This work has the purpose of exposing the importance of biocuration of biodiversity databases, explaining the curating process carried out in Biotica©, which is CONABIO´s Information System, exemplifying some of the most common errors that occur in biological data such as: omission, typographical, contextual, redundancy, convention, uniformity and consistency, presenting some solutions, and discussing the importance of research and teaching of biocuration for biologists of 21st century.